2008
DOI: 10.1007/s00431-008-0857-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of the acceptability of antibiotic syrups, suspensions, and oral solutions prescribed to pediatric outpatients

Abstract: This observational study was designed to evaluate the acceptability of oral antibiotics (including generics) commonly prescribed to children by community practitioners in France. Between February and July 2006, the parents of 953 children enrolled by 46 pediatricians completed a questionnaire, including a taste assessment based on representations of five facial expressions. The proportions of "satisfactory" taste judgments showed a significant difference between amoxicillin-clavulanate reference product and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…Palatability is so significant in ensuring successful administration of a course of treatment that a recent call has been made for the evaluation of palatability and taste before European marketing authorisation is granted 11. Current European Parliament legislation12 also emphasises the importance of making new drugs more acceptable.…”
Section: Adherence and Tastementioning
confidence: 99%
See 2 more Smart Citations
“…Palatability is so significant in ensuring successful administration of a course of treatment that a recent call has been made for the evaluation of palatability and taste before European marketing authorisation is granted 11. Current European Parliament legislation12 also emphasises the importance of making new drugs more acceptable.…”
Section: Adherence and Tastementioning
confidence: 99%
“…The use of universal, standardised visual analog scales to quantify a child's response to the taste of a medicine (eg, the facial hedonic method) are widely described throughout the literature 6 8 10 11 21. One study has shown that the hedonic method is worse than own spontaneous verbal judgements at discriminating between taste differences in children under 6 years of age, although both methods are equally effective for older children 21.…”
Section: Palatabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies compare the acceptance and flavour preferences of a spectrum of drugs from one class (e.g. antibiotics) using a "one-off" taste test method, commonly with the aid of a visual analogue scale (VAS) most often in healthy children or adults (Bagger-Sjöbäck and Bondesson, 1989;Chan et al, 1997;Cohen et al, 2009;El-Chaar et al, 1996;Samulak et al, 1996;Toscani et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory analysis is a stage of product development that analyzes and interprets the reactions produced by its features. Ideally should be performed whenever a new formulation is introduced in a given context [28][29][30].…”
Section: Introductionmentioning
confidence: 99%